Academic and Non-Academic Determinants of Student Satisfaction in Muslim Higher Education - La Diadhan Hukama (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study aims to analyze the influence of Academic Aspect and Non-Academic Aspect on student satisfaction among Muslim undergraduate students at a university in Jakarta. The study employed a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) with WarpPLS 6.0. Data were collected through questionnaires distributed to 238 final-year students selected using purposive sampling. The results indicate that both Non-Academic Aspect and Academic Aspect have positive and significant effects on student satisfaction. These findings suggest that the quality of academic experiences, administrative services, campus facilities, and institutional support play important roles in shaping students’ educational experiences and satisfaction within higher education institutions. Academic quality reflected through lecturer competence, learning processes, and curriculum relevance contributes positively to students’ perceptions of institutional quality.